IMPLEMENTASI PELAYANAN KESEHATAN PESERTA BADAN PENYELENGGARA JAMINAN SOSISIAL (BPJS) DI KAJI DARI UNDANG – UNDANG NO.24 TH.2014 DI RSUD DR. SOEWONDO KENDAL - Suwarji Suwarji; Ikka Puspita Sari (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2022)
The implementation of social insurance for all citizens as mandated in Article 28H Constitution of the Republic of Indonesia in 1945, Amendment IV, Paragraph (1), (2) and (3) Chapter XA of the right to social security which say: Each person has a right to a life of well-being in body and mind, to a place to dwell, to enjoy a good and healthy environment, and to receive medical care. Each person has the right to facilities and special treatment to get the same opportunities and advantages in order to reach equality and justice. Each person is entitled to social security enabling him to develop his entire self unimpaired as a dignified human being. Through the enactment of Law No. 40 of 2004 on the Social Security, the Indonesian nation has actually had a social insurance system for all Indonesian people. In accordance with the article 5 of the Law mandates the establishment of the agency called the Social Security Agency (BPJS) which on November 25, 2011, stipulated Law No. 40 of the National Social Security System and Law No. 24 of 2011 on the Social Security Agency (BPJS) which commenced on January 1, 2014. The aim of this study is to analyze the quality of the implementation of healthcare service, the payment system and factors obstracting it. This study uses descriptive qualitative methodology with informants representing the health care workers and health service user or patients. The data was collected by using in-depth interview and field observation. Qualitative data analysis was conducted to answer the problem of research in the form of data reduction that is described in narrative. Based on the result, it revealed that the implementation of Health Care For BPJS Participants studied of constitution No. 24 of 2011 in dr. H. Sowondo Kendal in general has been running well according to Standard Operational referring to the public services Law No. 25 of 2009.